Prognostic Impact of Organomegaly in Mastocytosis: An Analysis of the European Competence Network on Mastocytosis - Lübke, Johannes; Schwaab, Juliana; Christen, Deborah; Elberink, Hanneke Oude; Span, Bart; Niedoszytko, Marek; Gorska, Aleksandra; Lange, Magdalena; Gleixner, Karoline V; Hadzijusufovic, Emir; Solomianyi, Oleksii; Angelova-Fischer, Irena; et al. (The journal of allergy and clinical immunology. In practice, 2023)
BACKGROUND: Organomegaly, including splenomegaly, hepatomegaly, and/or lymphadenopathy, are important diagnostic and prognostic features in patients with cutaneous mastocytosis (CM) or systemic mastocytosis (SM). OBJECTIVES: To investigate the prevalence and prognostic impact of 1 or more organomegalies on clinical course and survival in patients with CM/SM. METHODS: Therefore, 3155 patients with CM (n = 1002 [32%]) or SM (n = 2153 [68%]) enrolled within the registry of the European Competence Network on Mastocytosis were analyzed. RESULTS: Overall survival (OS) was adversely affected by the number of organomegalies (OS: #0 vs #1 hazard ratio [HR], 4.9; 95% CI, 3.4-7.1, P < .001; #1 vs #2 HR, 2.1, 95% CI, 1.4-3.1, P < .001; #2 vs #3 HR, 1.7, 95% CI, 1.2-2.5, P = .004). Lymphadenopathy was frequently detected in patients with smoldering SM (SSM, 18 of 60 [30%]) or advanced SM (AdvSM, 137 of 344 [40%]). Its presence confered an inferior outcome in patients with AdvSM compared with patients with AdvSM without lymphadenopathy (median OS, 3.8 vs 2.6 years; HR, 1.6; 95% CI, 1.2-2.2; P = .003). OS was not different between patients having organomegaly with either ISM or SSM (median, 25.5 years vs not reached; P = .435). At time of disease progression, a new occurrence of any organomegaly was observed in 17 of 40 (43%) patients with ISM, 4 of 10 (40%) patients with SSM, and 33 of 86 (38%) patients with AdvSM, respectively. CONCLUSIONS: Organomegalies including lymphadenopathy are often found in SSM and AdvSM. ISM with organomegaly has a similar course and prognosis compared with SSM. The number of organomegalies is adversely associated with OS. A new occurrence of organomegaly in all variants of SM may indicate disease progression.
Keywords: Mastocytosis, Cutaneous; prognóza; Prognosis; Mastocytosis; lymfadenopatie; systémová mastocytóza; kožní mastocytóza; mastocytóza; lidé; progrese nemoci; Lymphadenopathy; Disease Progression; Mastocytosis, Systemic; Humans